Exploring corrosion protection of La-Fe-Si magnetocaloric alloys by passivation. (August 2016) - Gebert, Annett; Krautz, Maria; Waske, Anja
Abstract: Magnetocaloric La(Fe, Si)13 -based alloys are promising materials for magnetic cooling systems but their limited corrosion resistance in water-based heat transfer fluids is critical. The corrosion behavior of as-cast and annealed La-Fe-Si alloy samples was analyzed in comparison to that of La and Fe for evaluation of the impact of alloy chemistry and microstructure. Electrochemical studies were conducted in defined electrolytes starting with aerated distilled water (pH = 6) for assessing the influence of pH value changes and anion contaminations. Specifically, forced flow electrolyte conditions were applied which are closer to operation conditions of real magnetocaloric regenerator beds than stagnant ones. Corroded sample surfaces were analyzed with SEM to assess damage mechanisms. The reactive nature of the alloy constituents determines the high corrosion activity and limited passivation ability of La-Fe-Si alloys. Their exposure to distilled water is particularly detrimental under stagnant conditions as local fluid acidification enhances corrosion processes. These are based on galvanic coupling between the phases with different corrosion activities: La-rich phases > La(Fe, Si)13 -based matrix > alpha-Fe(Si). Laminar fluid flow is beneficial for alloy surface passivation. But anion contaminants like sulfate or hydrogen phosphate ions counteract the weak passivity in flowing distilled water. While acidic conditions lead to instable corrosive states, a pH value control of the heat transfer fluid at alkaline conditions is effective for stable passivity of the alloy surface. Also, the applicability of a phosphate conversion coating treatment in 0.15 M NaH2 PO4 (pH = 4) was evaluated and prospects of this approach are discussed. Highlights: Reactive nature of alloy constituents determines high corrosion activity of La-Fe-Si. Local corrosion due to phase reactivity: La-rich > La(Fe, Si)13 matrix > alpha-Fe(Si). Flow of heat transfer fluid and alkaline conditions are beneficial for passivation. Anions (sulphate, hydrogen phosphate) disturb passivity in flowing distilled water.